2010
DOI: 10.1007/s10482-010-9460-2
|View full text |Cite
|
Sign up to set email alerts
|

A guide to successful bioprospecting: informed by actinobacterial systematics

Abstract: New structurally diverse natural products are discovered when novel screening procedures are introduced or when high quality biological materials from new sources are examined in existing screens, hence it is important to foster these two aspects of novelty in drug discovery programmes. Amongst prokaryotes, actinomycetes, notably streptomycetes, remain a rich source of new natural products though it has become increasingly difficult to find such metabolites from common actinomycetes as screening 'old friends' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
200
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(212 citation statements)
references
References 198 publications
(199 reference statements)
3
200
1
1
Order By: Relevance
“…The discovery of candidate novel taxa shown in the present work supports the opinion of Strobel and Daisy (2003) that endophytes are a rich and reliable source of genetic diversity and novel as yet undescribed species. Actinobacteria are well known as a rich source of antimicrobial agents, and many useful antibiotics have been prepared from them (Goodfellow and Fiedler 2010). Many isolates obtained in this study showed antimicrobial, especially anti-phytopathogenic, activity in vitro.…”
Section: Discussionmentioning
confidence: 63%
“…The discovery of candidate novel taxa shown in the present work supports the opinion of Strobel and Daisy (2003) that endophytes are a rich and reliable source of genetic diversity and novel as yet undescribed species. Actinobacteria are well known as a rich source of antimicrobial agents, and many useful antibiotics have been prepared from them (Goodfellow and Fiedler 2010). Many isolates obtained in this study showed antimicrobial, especially anti-phytopathogenic, activity in vitro.…”
Section: Discussionmentioning
confidence: 63%
“…They contain LL-diaminopimelic acid in the cell-wall peptidoglycan and no diagnostic sugars in whole-cell hydrolysates (Kämpfer, 2012). Strains of species of the genus Streptomyces are the source of a broad range of secondary metabolites, notably antibiotics (Bérdy, 2005;Goodfellow & Fiedler, 2010), and are distributed in various environments including soils, freshwater and marine environments (Kämpfer, 2012).…”
mentioning
confidence: 99%
“…2 Such organisms include neutrotolerant acidophilic streptomycetes which grow from pH 4.5 to 7.5, with an optimum between pH 5.0 and 5.5. 3 Members of this group were isolated from a hay meadow soil taken from Cockle Park Experimental Farm in Northumberland, UK.…”
mentioning
confidence: 99%